Selecting appropriate process models for IT projects: Towards a tool-supported decision approach - Harr, Michael; Seufert, Sarah (Wirtschaftsinformatik (WI) 2023 Proceedings, 2023)
The appropriate selection of suitable process models plays an important role for IT project success. To aid in decision-making, IT project management literature offers a plethora of decision models for selecting suitable process models, however, hybrid process models are often neglected and adoption in practice is low or non-existent. To address this challenge, we draw on contingency theory to develop and implement a tool-supported decision model for the selection and evaluation of appropriate process models for IT projects, thereby leveraging artificial intelligence and machine learning in the context of a self-enforcing network. Our model provides an objective tool to assess process model suitability. Results from a conducted online survey with project management experts indicate high validity. Therefore, we contribute to the field of IT project management by expanding AI-based decision models for selecting and evaluating process models through extending the range of covered models and implementing inherent weighting of criteria.
Keywords: IT Project Management; Process Models; Decision Model; Self-Enforcing Network; Contingency Theory.